Cu(In, Ga)Se2 monograin powders with different Ga content for solar cells. (December 2018) - Timmo, K.; Kauk-Kuusik, M.; Pilvet, M.; Altosaar, M.; Grossberg, M.; Danilson, M.; Kaupmees, R.; Mikli, V.; Raudoja, J.; Varema, T.
Highlights: CIGSe monograin layer solar cell with efficiency of 12.8% is developed. Optimal Ga content for the CuIn1-x Gax Se2 monograin layer solar cells is x = 0.21. Deep photoluminescence emission is detected in Ga-rich CuIn1-x Gax Se2 monograins. Eg ∗ increased from 1.0 eV to 1.68 eV by changing the Ga content from 0 to 1.0. The smallest tetragonal distortion with lattice ratio c/a = 2.0 was observed at x = 0.21. Abstract: Monograin layer (MGL) solar cell technology based on CuIn1-x Gax Se2 (CIGSe) monograin powder crystals is a promising approach for the future low-cost production of flexible solar panels. In this study, CuIn1-x Gax Se2 monograin powders (0 ≤ x ≤ 1) were prepared from binary compounds in the liquid phase of potassium iodide as flux material in evacuated quartz ampoules at 720 °C. The crystal structure and the lattice parameters of the CIGSe monograin powder crystals were determined by using X-ray diffraction analysis. A linear decrease of the lattice parameters with increasing Ga concentration was detected. The photoluminescence (PL) spectra of the CIGSe crystals were dominated by the edge emission band that shifted towards higher energies with increasing Ga content. Moreover, additional deep PL band (below 1.0 eV) appeared for Ga contents above x = 0.21 showing higher relative intensity with increasing Ga content. The effective bandgap energy of the CIGSe monograin powder materials ranged from 1.0 eV to 1.68 eV as the [Ga]/([In] + [Ga]) ratio increased from 0 to 1.0. An efficiency of 12.8% (active area) was obtained with the MGL solar cell based on CuIn1-x Gax Se2 monograin powder with Ga content of x = 0.21.